التصوف في فكر مالك بن نبي - محجوب, خالد (جامعة الوادي university of eloued, 2022)
يهدف هذا البحث إلى بيان موقف مالك بن نبي رحمه الله من التصوف، كما يهدف إلى التحقيق في تموضع الفكر الإصلاحي لمالك بن نبي في جانبه الأخلاقي، في إطار النسق العام لمرجعية علماء الغرب الإسلامي، حيث بدا لنا بعد البحث والتمحيص أن البعد الأخلاقي أو الصوفي كان حاضرا بقوة في كتابات مالك بن نبي، إلى درجة اعتباره روح المشروع الحضاري الذي قدمه ابن نبي تحت عنوان " مشكلات الحضارة". This research aims to clarify the position of Malik bin Nabi, from Sufism, and also aims to investigate the positioning of the reformist thought of Malik bin Nabi in its moral aspect, within the framework of the general system of reference of the scholars of the Islamic West. He was strongly present in Malik bin Nabi's writings, to the point of being considered the spirit of the civilizational project presented by Malik bin Nabi under the title "The Problems of Civilization
مقال
Keywords: مالك بن نبي؛ التصوف؛ الحضارة؛ الاصلاح؛ التربية; Malik bin Nabi; Sufism; civilization; reform; education